Análisis a los estados financieros de la unión provincial de cooperativas de transporte de Sucumbíos, provincia de Sucumbíos periodo 2014 – 2015 - Pantoja Toro, Dayra Maritza (2017)
The present investigation, is framed within the parameters established in the corresponding Academic Regulations of the National University Of Loja, whose development is justified, because the managerial level of the company can know the reason for performance or not in the development of their daily operations, as well as may have a future idea about the permanence in the middle, another Of the benefits to the organization would be the control of material, economic and human resources so that decisions will be made reliable and timely. The investigative work carried out in accordance with the reality of the business problem was developed in compliance with the following general objective: Analysis of the Financial Studies of the Union Province of Cooperatives of Transport of Sucumbíos, of the city of Lago Agrio, Province of Sucumbíos, period 2014 - 2015, for future decision making; In addition the following specific objectives were fulfilled; The methods of analysis, both horizontal and vertical, were applied to the financial statements and the variations for the periods 2014-2015 were determined; The financial indicators, which are adjustable to the company, were applied, in addition an analysis was presented through a report of the results obtained in which the application of the analysis to the financial statements was evidenced; Finally the financial statements for five years were projected, which will serve as support for future decision making in the Union of Transport Cooperatives of Sucumbíos. Finally, it was possible to conclude that with the application of the financial indicators it was evidenced that in the periods of analysis, the company had the necessary liquidity to face financial risks and to maintain its operations therefore had degree of independence, however most of the Credit risk, the entire asset item could have been financed by equity; The profitability of the invested capital was higher than the cost of the capital provided and although there was an insufficient sales account in a period, the company showed a good collection policy, and finally in the two periods the shareholders did not have the expected profitability of the company.